Wittgenstein's Philosophical investigations an introduction - Stern, David G. (Cambridge University Press, 2004)
In this new introduction to a classic philosophical text, David Stern examines Wittgenstein's Philosophical Investigations. He gives particular attention to both the arguments of the Investigations and the way in which the work is written, and especially to the role of dialogue in the book. While he concentrates on helping the reader to arrive at his or her own interpretation of the primary text, he also provides guidance to the unusually wide range of existing interpretations, and to the reasons why the Investigations have inspired such a diversity of readings. Following closely the text of the Investigations and meant to be read alongside it, this survey is accessible to readers with no previous background in philosophy. It is well-suited to university-level courses on Wittgenstein, but can also be read with profit by students in other disciplines
Title from publisher's bibliographic system (viewed on 05 Oct 2015)
Keywords: Wittgenstein, Ludwig / 1889-1951 / Philosophische Untersuchungen; Wittgenstein, Ludwig -- 1889-1951 -- Philosophische Untersuchungen; Philosophie; Sprache; Language and languages / Philosophy; Philosophy